2009
DOI: 10.1002/eji.200838956
|View full text |Cite
|
Sign up to set email alerts
|

Role of T cell TGF‐β signaling in intestinal cytokine responses and helminthic immune modulation

Abstract: Colonization with helminthic parasites induces mucosal regulatory cytokines, like IL-10 or TGF-b, that are important in suppressing colitis. Helminths induce mucosal T cell IL-10 secretion and regulate lamina propria mononuclear cell (LPMC) Th1 cytokine generation in an IL-10-dependent manner in WT mice. Helminths also stimulate mucosal TGF-b release. As TGF-b exerts major regulatory effects on T lymphocytes, we investigated the role of T lymphocyte TGF-b signaling in helminthic modulation of intestinal immuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
77
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 36 publications
(59 reference statements)
7
77
0
Order By: Relevance
“…1). TGF-b is a key cytokine in H. polygyrus-induced immune regulation (33), with the capacity to block Ag-specific CD4-T cell activation, as shown above, and with the potential to downmodulate the migratory capacity of DCs (34). To test whether worm-derived molecules and TGF-b could influence BCG-induced DC migration, we conditioned the footpad with TGF-b or HES 10 d prior to BCG inoculation.…”
Section: H Polygyrus Infection Reduces Bcg Triggered Migration Of DCmentioning
confidence: 99%
“…1). TGF-b is a key cytokine in H. polygyrus-induced immune regulation (33), with the capacity to block Ag-specific CD4-T cell activation, as shown above, and with the potential to downmodulate the migratory capacity of DCs (34). To test whether worm-derived molecules and TGF-b could influence BCG-induced DC migration, we conditioned the footpad with TGF-b or HES 10 d prior to BCG inoculation.…”
Section: H Polygyrus Infection Reduces Bcg Triggered Migration Of DCmentioning
confidence: 99%
“…Cytokines are a group of small and soluble molecules, e.g. interleukins, interferons, and tumour necrosis factors which have a key role in the proliferation of immunocytes, apoptosis, and immune modulation [9,10,11]. Teleosts represent the foremost fish species with typical adaptive immune and innate immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…1 Collectively, these studies have shown that as a consequence of the host response to infection with helminth parasites, there is mobilization of transforming growth factor (TGF)-␤, interleukin (IL)-10, Foxp3 ϩ regulatory T cells, alternatively activated macrophages, and inhibition of IL-17-and interferon (IFN)-␥-driven events: one, or a combination, of these events could block the development of autoimmune and inflammatory disorders. [2][3][4][5][6][7] These findings have been complemented by intriguing data suggesting that infection with viable parasitic nematodes could be a treatment for patients with inflammatory bowel disease (IBD) 8 or asthma, 9 whose condition is not managed by conventional therapies.…”
mentioning
confidence: 99%